2011
DOI: 10.1111/j.1440-0960.2011.00842.x
|View full text |Cite
|
Sign up to set email alerts
|

Toxic epidermal necrolysis‐like subacute cutaneous lupus erythematosus

Abstract: Toxic epidermal necrolysis (TEN)-like presentations have been described in non-drug-induced settings. We describe a case of subacute cutaneous lupus erythematosus (SCLE) in a 53-year old woman, which evolved into a TEN-like presentation over the course of 4 weeks. The patient responded rapidly to treatment with intravenous methylprednisolone. This article draws attention to features that may be used to differentiate classical TEN from TEN-like SCLE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…Lastly in Leckie's study, a 65 years old diagnosed with rheumatoid athritis for almost 9 year, after 2 weeks addition of 200mg/day of HCQ and developing SJS, it reported that she respond with steroids (14). In addition, in previous studies, there are cases shows the association of using steroid to develop SJS in SLE patients (13,15,16,17,18). Our patient had HCQ and prednisolone intake.…”
Section: Discussionsupporting
confidence: 51%
“…Lastly in Leckie's study, a 65 years old diagnosed with rheumatoid athritis for almost 9 year, after 2 weeks addition of 200mg/day of HCQ and developing SJS, it reported that she respond with steroids (14). In addition, in previous studies, there are cases shows the association of using steroid to develop SJS in SLE patients (13,15,16,17,18). Our patient had HCQ and prednisolone intake.…”
Section: Discussionsupporting
confidence: 51%
“…The differentiation between TEN and TEN-like CLE can be distinguished by a history of drugs used, clinical presentation, serology, histopathology and DIF studies. [2][3][4][5][6][7] Most patients with TEN-like CLE have no history of medications and have a clinical background of SLE. Cutaneous lesions are usually a gradual progression of the blistering eruptions that predominate on the photo distribution with minimal or limited mucosal involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Vesiculobullous annular SCLE is mainly characterized by erosion and crusting, and more rarely by vesicles and bullae occurring at the active advancing edge of annular SCLE lesions or at the center of the plaque 5,16. Like ACLE, TEN-like sheets of epidermal cleavage evolving from typical photodistributed nonscarring annular or papulosquamous SCLE have rarely been reported 16,23,24. The onset of TEN-like SCLE is gradual.…”
Section: Le-specific Vesiculobullous Diseasesmentioning
confidence: 99%
“…The onset of TEN-like SCLE is gradual. Nikolsky's sign can be either positive or negative, and mucosal involvement is usually absent or minimal 24. Most cases of SCLE-associated vesiculobullous disease lack visceral-organ involvement 22…”
Section: Le-specific Vesiculobullous Diseasesmentioning
confidence: 99%